APPLICATION OF COLLABORATIVE PROBLEM-BASED LEARNING TO IMPROVE THE QUALITY OF TEACHING AND LEARNING ON APPLIED LINGUISTICS - Sujito Sujito; Wildan Mahir Mauttagien (Center of Language and Cultural Studies [CLCS], 2016)
This study presents teaching process in applied linguistics course using Collaborative Problem-Based Learning (CPBL). The objectives are to see how CPBL increases: (1) students’ active involvement in classroom activities, (2) lecturer-students and students-students communicative interaction, (3) students’ creativity in finishing projects, (4) students’ cognitive comprehension, and (5) level of students’ satisfaction/ positive response to the implementation of CPBL. This study used a two cycle Classroom Action Research using descriptive approach. The subjects were 3 classes with 30 students each Applied Linguistic Course of English Department of IAIN Surakarta. This study revealed that students’ motivation, communicative interaction, students’ creativity in finishing projects, cognitive comprehension and students’ satisfaction/ positive response to the implementation of problem based learning in Applied Linguistics course attained significant improvement.